Numerical integration of bivariate functions over a non rectangular area by using fluctuationlessness theorem - (:unkn) unknown (My University, 2009)
"Fluctuation free matrix representation approximation Method" developed by M. Demiralp can be used in approximating the multiple remainder terms of the integral of the Multivariate Taylor expansion. This provides us with a new numerical integration method for multivariate functions. However in this paper instead of dealing with a single formula which takes care of the multiple remainder terms, a new approach is undertaken. At every step of a multivariate integration only one variable is taken care of. Thus an iterative procedure which speeds up the computation rate is obtained.
Keywords: Explicit Remainder Term; Fluctuationlessness Theorem; Multivariate Functions; Numerical Integration; Taylor Expansion